If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(d+1)+4=19
We move all terms to the left:
3(d+1)+4-(19)=0
We add all the numbers together, and all the variables
3(d+1)-15=0
We multiply parentheses
3d+3-15=0
We add all the numbers together, and all the variables
3d-12=0
We move all terms containing d to the left, all other terms to the right
3d=12
d=12/3
d=4
| 0=-16t^2+47t-30 | | 9−(6−8x)=4x+5 | | 3(2x-6)=2(3x-4) | | -8-8b=-10b | | 4+x=41 | | 130+0.60x=50+0.80x | | 3u+39=-2(u+3) | | -2t^2+13t-15=-(t-5)(2t-3) | | 49y=6(8y+6) | | 49-11x=11+8x | | 130+0.60x=50+0.80 | | (5x-3)/(x+8)=0 | | 4x^+12=3x^+13 | | -5(3x-2)=3(1-4x)+12 | | 2g+3=6-13 | | -2+2y=10 | | -9.9y=-80.19 | | 4k+1.72=1.54+12.2k | | 49y=6( | | 9x+3=-42 | | 2/3g+1/2=5/2 | | 6/3x=40/3+7/3x | | 16=2(c+6) | | 41+x=70 | | -6(-1-3x)=-2(x+7) | | 2x-0.25x=1.4 | | 12/g=6/10 | | -8–8b=-10b | | 6-6x=7x-9x-x | | 9(3x+7)-4(6x+7)-1=(-3x)+35 | | 7(x+5)=-7x+5) | | t=3+21.83 |